2009
DOI: 10.1097/ans.0b013e3181a3d754
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of HIV Education on the Lives of Ugandan Nurses and Nurse-Midwives

Abstract: In this ethnography, I explored the impact of an HIV/AIDS education program on the lives of 24 Ugandan nurses and nurse-midwives. Nurses who previously had viewed themselves simply as providers of advice and sympathy now saw themselves as more holistic, collaborative caregivers. They voiced an increased awareness of their role as leaders and advocates in the community with respect to policy. The education program had positive and synergistic effects on the nurses' professional practice, communication and probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Studies in Nigeria, India, and Vietnam for example, found that training on changing knowledge and attitudes about HIV/AIDS [ 128 , 129 ], and participatory processes whereby hospital staff develop action plans or policies to address stigma and discrimination [ 129 , 130 ] helped to improve attitudes towards HIV positive patients. Similarly, in Uganda, an education program on HIV for nurses and nurse-midwives had a positive effect on professional practice, communication, and self-confidence [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Nigeria, India, and Vietnam for example, found that training on changing knowledge and attitudes about HIV/AIDS [ 128 , 129 ], and participatory processes whereby hospital staff develop action plans or policies to address stigma and discrimination [ 129 , 130 ] helped to improve attitudes towards HIV positive patients. Similarly, in Uganda, an education program on HIV for nurses and nurse-midwives had a positive effect on professional practice, communication, and self-confidence [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also came to understand the power of education to motivate and prepare themselves for leadership and advocacy roles with respect to policy development and other forms of political action. Full details of the study are provided elsewhere (Harrowing, 2009); in this article we focus on moral distress, which emerged as a dominant theme in the data.…”
Section: Author(s)mentioning
confidence: 99%
“…Participants provided numerous examples of utilising what they learned in multiple domains. This outcome resembles those of other successful interventions in SSA that provide healthcare workers with specialised HIV-prevention training (Harrowing, 2009;Kaponda et al, 2009). In another effective intervention, Islamic religious leaders received specialised schistosomiasis-prevention training (Celone et al, 2016).…”
Section: Discussionmentioning
confidence: 60%